Development and evaluation of a spray drying microencapsulation process for water-insoluble milk protein capsules. (October 2016) - Würth, R.; Foerst, P.; Kulozik, U.
Abstract: A spray drying process for water-insoluble milk protein capsules was developed, based on the classical rennet gelation mechanism. The process consisted of an initial gelation during drying and a final gelation under controlled rehydration conditions. A rheological characterisation of the feed solution with different total solid (TS) contents was carried out to determine the process limiting concentration. The maximal TS content was 35% to prevent premature gelation. Additionally, the rehydration temperature-dependent capsule-forming behaviour was characterised by sodium dodecylsulphate polyacrylamide gel electrophoresis and particle size measurements. In addition to the rehydration temperature, the product and process parameters during spray drying, such as initial TS content, feed rate and drying temperature, showed a great impact on the final capsule formation behaviour. A degree of aggregation (DA) of 80% was achieved using a combination of low TS and high feed rate, which shows that complete capsule formation after rehydration is possible.